CARA MENGHITUNG ZAKAT PERDAGANGAN EMAS DAN PENERAPANNYA OLEH PEDAGANG EMAS DI PASAR SENTRAL WATAMPONE - Abdulahanaa Abdulahanaa (Institut Agama Islam Negeri Bone, 2021)
Gold traded zakat can be seen from two sides, namely from the side of gold and from the side of trade. As a result, in the field there are differences in how to calculate the amount of zakat, determine the nisab, haul and the time of distribution. The existence of these differences causes no standard unit used, so that it has an impact on the weak legal certainty of gold traded zakat, so that it needs to be handled by scholars and academics by first doing research. This study aims to determine the practice of gold traded zakat in Watampone as the basis for the formulation of standard guidelines of gold trade zakat which will be disseminated to gold traders in order to create uniformity and legal certainty. This research is a field research with a normative approach. The population of this research is Muslim gold traders who have assets that meet the requirements of zakat in Watampone Central Market. The sampling technique was carried out by means of random sampling. Data collection was carried out by direct interviews and questionnaires. The data analysis method used was descriptive qualitative. After conducting the research, it was found that the gold traders at the Watampone Central Market did two ways in the process of calculating and distributing zakat. There are those who count because of their gold (according to the Maliki school of thought), and some are counting because of their trade (according to the jumhur school of thought). There are those who combine gold merchandise with other capital including money (according to the jumhur school of thought), some are separating them (according to the Maliki school of thought). There are those who pay zakat in the form of money (according to the jumhur school of thought) and there are also those who issue zakat in the form of goods / gold (according to the Syafi'i school of thought). They use the same nisab, which is following the golden ratio, but the amount is different.